Still me - Reeve, Christopher, 1952-2004. (New York : Random House, 1998)
Reeve's autobiography is distinguished not only by the dignified candor with which he describes his utterly changed world but also by his emotional directness
Includes index.
Keywords: Reeve, Christopher, -- 1952-2004.; Actors -- United States -- Biography; Quadriplegics -- United States -- Biography